The Influence Of Governance And Company Size On Company Value With The Disclosure Of Social Responsibility As A Mediation Variable In Food And Beverages Companies For The 2019-2021 - Siti Nurdiana Indah; Irvan Noormasyah (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2023)
This research aims to determine the influence of governance and company size on company value with disclosure of corporate social responsibility as a mediating variable. This research uses an associative research method with a quantitative approach, which is measured using a multiple linear regression method using the Statistical Program for Social Science (SPSS) version 25. The population in this research is food and beverages companies registered on the BEI for the 2019-2021 period. The data collection technique used purposive sampling which obtained 19 research samples with an observation period of 3 years for a total of 57 samples. The results of this research show that Independent Board of Commisioners influence company value. Audit Committee has an effect on company value. Company size influences company value. Independent Board of Commisioners have no effect on company value through Corporate Social Responsibility disclosure. Audit Committee has no effect on company value through Corporate Social Responsibility disclosure. Company size influences company value through Corporate Social Responsibility disclosure.